Screening and Phenotypic Diversity of Amylase Producing Rhizospheric Bacteria from Some North African Plants. (2016) - Choubane, Slimane; Cheba, Ben Amar; Benourrad, Amina
Abstract: Plant Growth Promoting Rhizobacteria (PGPR) are gaining interest because of their positive effect on plant growth and defense. Among these effects some enzymes secreted by PGPR are used by the plant in nutrient uptake and in biocontrol. The aim of this work is to isolate amylase producing bacteria from some North African plants rhizospheres. Amylases are starch degrading enzymes and can play a role in plant growth promoting by degrading organic matter in soil (starch). Total rhizospheric bacterial diversity was screened and Ceratonia ciliqua and Agrania spinosa showed the best results. Also, Caratonia ciliqua and Ficus carica isolates gave the best amylase production. Finally, crude amylase produced by Argania spinosa and Pistacia lentiscus had the best activities.